2010
DOI: 10.1590/s1982-56762010000200005
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate reductase-dependent nitric oxide synthesis in the defense response of Arabidopsis thaliana against Pseudomonas syringae

Abstract: Nitrate reductase (NR) was recently shown to play an important role during phytopathogenic interactions by providing substrates for the synthesis of nitric oxide (NO), a key signal for plant defense responses. In order to give additional support to this hypothesis, we compared NO-mediated defense responses of wild-type and NR double-deficient (nia1 nia2) Arabidopsis thaliana plants inoculated with the IBSBF-1115 (ibs) strain of Pseudomonas syringae pv. maculicola (Psm) and with genetically characterized avirul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Author's Personal copy osmotic stress or pathogen attack (Wang et al 2010;Kolbert et al 2010;Oliveira et al 2010). Therefore, we investigated the possible involvement of this enzyme in Cu 2?…”
Section: Plant Growth Regulmentioning
confidence: 99%
“…Author's Personal copy osmotic stress or pathogen attack (Wang et al 2010;Kolbert et al 2010;Oliveira et al 2010). Therefore, we investigated the possible involvement of this enzyme in Cu 2?…”
Section: Plant Growth Regulmentioning
confidence: 99%
“…In accordance with its key role in the nitrogen metabolism, C-NaR is highly regulated by complex transcriptional, translational, and posttranslational mechanisms that respond to nitrogen, carbon dioxide, and dioxygen availabilities, pH, temperature, and light. , ,, Noteworthy, C-NaR is rapidly degraded in darkness (half-life of 6 h). Besides this well-established role in the reduction of nitrate, C-NaR from different species were shown to also catalyze the subsequent nitrite reduction to NO (eq ), not only in vitro, , but also in vivo. The in vivo evidences for C-NaR-dependent NO generation were provided by studies with (i) transgenic plants expressing a permanently active C-NaR, ,, (ii) C-NaR knockout mutants ( nia 1 and nia 2 genes), , (iii) inactive C-NaR (e.g., plants with tungstate supply instead of molybdate), ,,− and (iv) others. ,,, The nitrite reduction by C-NaR was also studied in silico, and it was found that both nitrate and nitrite are easily reduced (to nitrite and NO, respectively), although, as expected, nitrate is the preferred substrate These two C-NaR activities, nitrate reductase and nitrite reductase, seem to be controlled by the dioxygen concentration.…”
Section: Biological Fate Of Nitritementioning
confidence: 99%
“…The C-NaR-dependent NO formation has been suggested to be involved in (i) stomatal closure, ,,,, (ii) onset of germination, (iii) phenylpropanoid metabolism, or (iv) immune defense mechanisms, because pathogen signals induce the C-NaR and increase the NO formation (strik­ingly similar to the mammalian inducible NOS). ,,,,, This enzyme is also suited to play a role as a cytoplasmatic nitrite sensor, to “signalize” the presence of toxic nitrite concentrations . In addition, C-NaR/nitrite may be acting not only as a NO source, but also as an oxygen sensor: it is intriguing that an enzyme that is rapidly degraded in darkness to avoid nitrite accumulation is increased during hypoxia, which also leads to nitrite accumulation.…”
Section: Biological Fate Of Nitritementioning
confidence: 99%
“…Interestingly, this occurs not only during O 2 deficiency but many other biotic- and abiotic-stress-induced reductive pathways of NO formation. For example, salinity stress, water deficiency, UV radiation, freezing, pathogen attacks, and wounding can trigger NO production in plants [ 38 , 39 , 40 , 41 , 42 , 43 ], which could be due to the fact that these stresses could lead to hypoxia and anoxia in plant tissues, while its formation could be a defense strategy to survive harsh conditions.…”
Section: Pathways Of No Formation During Hypoxia and Anoxiamentioning
confidence: 99%